Citron kinase controls a molecular network required for midbody formation in cytokinesis - Bassi, Zuni I. (National Academy of Sciences, 2013)
Cytokinesis partitions cytoplasmic and genomic materials at the end of cell division. Failure in this process causes polyploidy, which in turn can generate chromosomal instability, a hallmark of many cancers. Successful cytokinesis requires cooperative interaction between contractile ring and central spindle components, but how this cooperation is established is poorly understood. Here we show that Sticky (Sti), the Drosophila ortholog of the contractile ring component Citron kinase (CIT-K), interacts directly with two kinesins, Nebbish [the fly counterpart of human kinesin family member 14 (KIF14)] and Pavarotti [the Drosophila ortholog of human mitotic kinesin-like protein 1 (MKLP1)], and that in turn these kinesins interact with each other and with another central spindle protein, Fascetto [the fly ortholog of protein regulator of cytokinesis 1 (PRC1)]. Sti recruits Nebbish to the cleavage furrow, and both proteins are required for midbody formation and proper localization of Pavarotti and Fascetto. These functions require Sti kinase activity, indicating that Sti plays both structural and regulatory roles in midbody formation. Finally, we show that CIT-K’s role in midbody formation is conserved in human cells. Our findings indicate that CIT-K is likely to act at the top of the midbody-formation hierarchy by connecting and regulating a molecular network of contractile ring components and microtubule-associated proteins.